Use of grape polyphenols against carcinogenesis: Putative molecular mechanisms of action using in vitro and in vivo test systems - Gollucke, Andrea P. B.; Aguiar Júnior, Odair; Barbisan, Luis Fernando [UNESP]; Ribeiro, Daniel Araki (SAGE Publications, 2013)
Polyphenols are present in foods and beverages and are related to sensorial qualities such as color, bitterness, and astringency, which are relevant in wine, tea, grape juice, and other products. These compounds occur naturally in forms varying from simple phenolic acids to complex polymerized tannins. Thus, it is reasonable to expect that grape-derived products elaborated in the presence of skins and seeds, such as wine and grape juice, are natural sources of flavonoids in the diet. Carcinogenesis is a multistep process that is characterized by genetic, epigenetic, and phenotypic changes. With increasing knowledge of these mechanisms, and the conclusion that most cases of cancer are preventable, efforts have focused on identifying the agents with potential anticancer properties. The use of grape polyphenols against the carcinogenesis process seems to be a suitable alternative for either prevention and/or therapeutic purposes. The aim of this article is to show the molecular data generated from the use of grape polyphenols against carcinogenesis using in vivo and in vitro test systems. © Mary Ann Liebert, Inc. and Korean Society of Food Science and Nutrition.
Keywords: Cancer; Carcinogenesis; Grape polyphenol; anthocyanin; diethylnitrosamine; polyphenol derivative; resveratrol; antineoplastic activity; carcinogenesis; epigenetics; genetics; grape; human; in vitro study; in vivo study; molecular mechanics; nonhuman; phenotype; priority journal; red wine; review; Animals; Anticarcinogenic Agents; Antineoplastic Agents, Phytogenic; Diet; Fruit; Humans; Neoplasms; Phytotherapy; Plant Extracts; Polyphenols; Vitis